Long-term fine particulate matter exposure on lung cancer incidence and mortality in Chinese nonsmokers - Zhu, M; Han, Y; Mou, Y; Meng, X; Ji, C; Zhu, X; Yu, C; Sun, D; Yang, L; Sun, Q; Chen, Y; Du, H; et al. (American Thoracic Society, 2025)
Rationale: The association between fine particulate matter (PM2.5) and lung cancer incidence in non-smokers (LCINS) remains inconsistent.